Detection of Cola beverage by electronic nose - LU Xiao-li; HAI Zheng; WANG Jun (浙江大学学报. 农业与生命科学版)
There is little study on the detection of liquid beverage by electronic nose, and the effect is not satisfied. Three means of pretreatment: detected directly by electronic nose, processed by the enrichment and desorption unit (EDU) or processed by Na2CO3 as desiccant were adopted to detect Coca cola, pepsi cola and future cola by electronic nose. To review the effect of three pretreatment methods, principal component analysis and linear discriminant analysis were employed, and the result of analysis indicated that the experiment employing Na2CO3 as desiccant to pretreat the samples can improve the effect of detection significantly.